A new ZnO-ZnS-CdS heterostructure on Ni substrate: A binder-free electrode for advanced asymmetric supercapacitors with improved performance. (20th October 2022) - BiBi, Shagufta; Shah, Muhammad Zia Ullah; Sajjad, Muhammad; Shafi, Hafiz Zahid; Amin, B.; Bajaber, Majed A.; Shah, A.
Abstract: ZnO is an appealing electrode material for supercapacitors due to its high capacitance, low cost, environmental friendliness, and good electrochemical reversibility. In this paper, we present the synthesis of a newly designed ZnO covered with ZnS and paired with CdS to produce a ternary heterostructure. According to the morphological research, ZnO has an urchin-like shape coated with ZnS and CdS nanoparticles on the surface with no undesired by-product residues, which improves the surface functionalities. First, we combined ZnO and ZnS to make a binary nanocomposite that outperformed its bulk equivalent ZnO by 322 mAh g −1 at 175 mAh g −1 during the charge-discharge process when a low current flow of 1 A g −1 was used. Meanwhile, the synergistic effect of multiple components, a new class of ternary ZnO-ZnS-CdS heterostructure was developed which effectively improved the electrochemical properties of the individual constituents, e.g., a capacity of 434 mAh g −1, and charged transfer kinetics (over pristine ZnO, and ZnO-ZnS electrodes). Inspired from the good capacitive behavior in a three-electrode mode, we further assembled an ASC that exhibits exceptional energy-storage performance of 36 Wh kg −1, 5422 W kg −1 after adding an optimal voltage (1.8 V), and retain only ∼91% at a higher current response. Last but not least, compositing is a vital strategy to boost the overall capacitive performance of the nanomaterials.